Bahr al-Mahabba fi Asrār al-Mavadda: Literary-Mystical Interpretation of Surah Yusuf (PBUH) and New Insights about It - Mahboobe Shamshirgarha (Alzahra University, 2021)
Bahr al-Mahabba fi Asrār al-Mavadda is one of the Sufi commentaries in Arabic in which Surah Yusuf (Joseph Chapter) has been interpreted in a simple and pleasant prose along with some mystical points, allusions, and anecdotes. Four Persian translations of the work have been done over the last century due to its appealing content and significance. However, no critical review and correction of the book or accurate information about it, like its author, time of authorship, origin, formation, and its status in the mystic tradition of interpreting the Qur'an could be found. This commentary was composed with a practical approach to mysticism and in compliance with religious law and ethics, within the context of Sufi interpretive tradition in the early centuries of Islam (before the seventh century). This work, of which there are several editions, is sometimes attributed to Abu al-Futuh Ahmad al-Ghazali and sometimes to his older brother, Abu Hamed Muhammad. However, it appears that both of these ascriptions are wrong. It seems that this work had been compiled by collecting and translating some Persian anecdotes and quotations from the earlier Islamic commentaries, especially Anis al-Muridin and Shams al-Majalis, Ons al-Muridin and Rawdat al-Muhibbin and Ghessa-ye Yusuf; works that had been written in Arabic four or five centuries earlier. The present study was conducted through examining the commentary and its available editions as well as analyzing the content of hand-written manuscripts, early centuries’ commentaries, and the studies that have been done to date.